Implications of Expected Changes in the Seller's Price in Name-Your-Own-Price Auctions - Fay, Scott; Laran, Juliano (Management Science, 2009)
The seller's threshold price in name-your-own-price auctions varies over time. However, consumers must bid without knowing when these variations occur because the threshold price is unobservable to them. This paper uses an analytical model and laboratory auctions to explore how the frequency of changes in the threshold price impacts consumer bidding behavior in name-your-own-price auctions. In particular, we consider how the frequency of these expected changes affects the optimal pattern of bid sequences (e.g., strictly increasing over time or following a nonmonotonic pattern). We find that when the probability of a price change is moderate, consumers may have an incentive to use nonmonotonic bidding patterns. Rather than steadily increasing their bids over time, consumers will, at some point in the bid sequence, decrease their bid. However, when the expected probability of a price change is very low or very high, consumers do not have an incentive to use nonmonotonic bidding patterns. Interestingly, impatient bidders are more likely to decrease their bids at some point in the bid sequence than patient bidders. Finally, we find that more frequent price changes may increase customer satisfaction.